2008
DOI: 10.1074/jbc.m706067200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Some Molecular Mechanisms Governing Autoactivation of the Catalytic Domain of the Anaplastic Lymphoma Kinase

Abstract: NPM/ALK is an oncogenic fusion protein expressed in ϳ50% of anaplastic large cell lymphoma cases. It derives from the t(2; 5)(p23;q35) chromosomal translocation that fuses the catalytic domain of the tyrosine kinase, anaplastic lymphoma kinase (ALK), with the dimerization domain of the ubiquitously expressed nucleophosmin (NPM) protein. Dimerization of the ALK kinase domain leads to its autophosphorylation and constitutive activation. Activated NPM/ALK stimulates downstream survival and proliferation signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 35 publications
6
47
2
2
Order By: Relevance
“…The following primers were used: rat MYCN (forward 5 0 -TGCCAACAGTGGCGAGCA-3 0 ; reverse autoactivation of the ALK kinase domain and the transformation ability of NPM-ALK. 40 In response to treatment with crizotinib tyrosine phosphorylation of Y1278 was clearly abrogated (Figures 3a-c, lane 2). We observed identical results when employing NVP-TAE684 as inhibitor (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…The following primers were used: rat MYCN (forward 5 0 -TGCCAACAGTGGCGAGCA-3 0 ; reverse autoactivation of the ALK kinase domain and the transformation ability of NPM-ALK. 40 In response to treatment with crizotinib tyrosine phosphorylation of Y1278 was clearly abrogated (Figures 3a-c, lane 2). We observed identical results when employing NVP-TAE684 as inhibitor (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Interactions of the A-loop ␣-helix with both the N-terminal and C-terminal lobes of the kinase and a hydrogen bond between Tyr 1278 and Cys 1097 from the N-terminal ␤-turn motif serve to stabilize the observed conformation. The fact that Tyr 1278 is phosphorylated upon formation of fully activated ALK underscores the inactive nature of the observed structures (40,41). The fully activated ALK kinase is expected to resemble the activated form of the insulin receptor kinase (IRK), the structure of which has been reported previously using the Tris-phosphorylated IRK kinase domain crystallized with a substrate peptide and an ATP analog (42).…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%
“…The fact that Tyr 1278 makes no specific hydrogen bonding interactions in this structure and is adjacent to the beginning of the disordered region of the A-loop is clearly suggestive of more facile autophosphorylation of this residue. As previous studies have shown that Tyr 1278 , the first residue in the activation loop YXXXYY motif, is a key driver of ALK activation, the R1275Q structure provides a structural rationale of the activating nature of this mutant (40,41).…”
Section: Crystallization Of the Alk Kinase Domain By In Situmentioning
confidence: 99%
“…It is well established that inappropriate activation of various tyrosine kinases represents one of the important mechanisms underlying tumorigenesis (1,2). NPM-ALK, an oncogenic fusion protein found exclusively in a subset of ALK-positive anaplastic large cell lymphoma, is believed to promote tumorigenesis via its constitutively active tyrosine kinase (3).…”
mentioning
confidence: 99%